Skin cancer induced by natural UV-radiation as an occupational disease–requirements for its notification and recognition - Diepgen, Thomas L.; Brandenburg, Stephan; Aberer, Werner; Bauer, Andrea; Drexler, Hans; Fartasch, Manige; John, Swen Malte; Krohn, Steffen; Palfner, Stefanie; Roemer, Wolfgang; Schuhmacher-Stock, Uta; Elsner, Peter (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
In Germany over 2.5 million employees have an increased risk of skin cancer due to their occupational exposure to natural UV-irradiation. The medical consultation board "Occupational diseases" of the Ministry of Labor and Social affairs has investigated the association between occupational UV-irradiation and skin cancer risk and recommends to add the following new occupational disease into the appendix1 of the German ordinance on occupational diseases: "Squamous cell carcinoma and multiple actinic keratosis due to natural UV-irradiation". In this article we report in the view of the German Society of Occupational and Environmental Dermatology (ABD) and the German Statutory accident insurance (DGUV), whose criteria have to be fulfilled for the notification and recognition of an occupational skin cancer due to natural UV-irradiation.
EVALuna2:9720